Performance Evaluation of the Protocol and Leadership Communication Division of the Regional Secretariat of Hulu Sungai Utara Regency - Naila Citra; Budi Kristanto (Dinasti International Journal of Education Management and Social Science, 2025)
This study aims to evaluate the performance of the protocol and leadership communication division of the regional secretariat of Hulu Sungai Utara Regency in 2025, focusing on the effectiveness of the protocol and communication functions in supporting responsive and transparent governance. This study uses a qualitative descriptive approach with a case study method, involving one researcher and six informants, consisting of one Head of Section, one Head of Subsection, two protocol staff, and two aides. The study was conducted from September to October 2025. The data were collected through in-depth interviews, observations, and literature studies and validated using source triangulation, member checks, and audit trails. The results of the study indicate that performance is in the good category in the aspects of productivity, responsiveness, and accountability, but is still weak in service quality and responsibility due to limited human resources, infrastructure, and budget. These findings confirm that improving bureaucratic performance is determined not only by the availability of resources but also by the effectiveness of internal coordination and managerial support. Theoretically, this study enriches the literature on public bureaucratic performance evaluation and recommends improving employee competency, providing adequate infrastructure, and implementing digital evaluation to strengthen the effectiveness of public services. The results of this study can be a basis for local governments in formulating policies to improve the performance of bureaucratic organizations that are more adaptive, efficient, and oriented toward quality public services.